The MECRI Nadiem Makarim’s “Freedom of Learning”: A Critical Study of John Dewey’s Pragmatic Philosophy - Yohannes Telaumbanua; Yalmiadi Yalmiadi; Titin Ritmi (Rumah Jurnal IAIN Bukittinggi, 2022)
“Freedom of Learning” is the MECRI Nadiem Makarim’s sensational policy. Its top goals are to provide students with freedom of thinking and urge teachers to shift their education paradigms from traditional to contemporary ones. However, the facts assume that such a policy is trumping up and secretly includes Indonesian education in a list of the secular capitalist-style curriculum. The facts seem biased and even counter-productive if they are left unexplored. Therefore, this study aimed to diagnose the meaning of the policy in John Dewey’s pragmatic philosophy and its effects. This was qualitative research. Observation was a technique for collecting the data. Miles and Huberman’s model was a technique for analyzing the data. Credibility and dependability were used to examine the validity of the data. The results showed that the implied meaning of Makarim’s freedom of learning policy is interpreted as a process of building students’ reality through interaction with their real life. Knowledge is based on students’ experiences and constructed using scientific methods. The teacher’s role is to develop the students’ critical and creative thinking skills through scientific process. The curriculum prepares students for changes, research and verification, and problem-solving activities. More importantly, the policy urges to bring the classes closer to digital technology and e-devices, arouses students’ global awareness and learning skills of the 7C’s X 3C’s + 1I’s. In conclusion, the policy aims to advance the value and quality of education for Indonesian in the current era of digital technology. “Merdeka Belajar” adalah kebijakan sensasional Mentri Pendidikan R.I. Nadiem Makarim yang tujuan utamanya adalah untuk memberikan mahasiswa kebebasan berpikir serta mendorong para guru untuk bisa merubah paradigma pendidikan mereka dari paradigma tradisional ke kontemporer. Namun, fakta berasumsi bahwa kebijakan semacam itu adalah sebuah rekayasa belaka dan secara diam-diam memasukkan pendidikan Indonesia ke dalam daftar kurikulum ala kapitalis sekuler. Fakta tersebut tampak bias dan bahkan kontra-produktif jika dibiarkan tidak dieksplorasi. Oleh karena itu, penelitian ini bertujuan untuk mendiagnosis makna kebijakan dalam filsafat pragmatis John Dewey dan efek yang menyertainya. Ini adalah penelitian kualitatif. Observasi merupakan teknik pengumpulan data. Model Miles dan Huberman adalah teknik untuk menganalisis data. Kredibilitas dan ketergantungan digunakan untuk menguji validitas data. Hasil penelitian menunjukkan bahwa makna tersirat dari kebijakan kebebasan belajar mentri Makarim dimaknai sebagai proses membangun realitas siswa melalui interaksi dengan kehidupan nyata mereka. Pengetahuan didasarkan pada pengalaman siswa dan dikonstruksi menggunakan metode ilmiah. Peran guru adalah mengembangkan kemampuan berpikir kritis dan kreatif siswa melalui proses ilmiah. Kurikulum berfokus pada mempersiapkan siswa untuk perubahan, penelitian dan verifikasi, dan kegiatan pemecahan masalah. Lebih penting lagi, kebijakan tersebut mendesak untuk membawa mahasiswa lebih dekat dengan penguasaan teknologi digital dan perangkat elektronik, membangkitkan kesadaran global siswa dan keterampilan belajar 7C’s X 3C’s + 1I’s. Kesimpulannya, kebijakan tersebut bertujuan untuk memajukan nilai dan kualitas pendidikan bagi masyarakat Indonesia di era teknologi digital saat ini.